Effects of Liqi Tongbian decoction on gut microbiota, SCFAs production, and 5-HT pathway in STC rats with Qi Stagnation Pattern - Qihong Liu; Danfeng Ke; Youqin Chen; Aling Shen; Liya Liu; Lunan Hu; Yan Ren; Wenyi Fang; Peilin Zhao; Thomas J. Sferraf; Yunfeng Luo; Xiao Ke (Frontiers in Microbiology, 2024)
Slow transit constipation (STC) is a common and debilitating condition characterized by delayed colonic transit and difficulty in fecal expulsion, significantly impacting patients’ physical and mental wellbeing as well as their overall quality of life. This study investigates the therapeutic potential of Liqi Tongbian Decoction (LTD) in the treatment of STC, especially in cases involving the context of Qi stagnation, through a multifaceted approach involving the modulation of intestinal flora and short-chain fatty acids (SCFAs). We employed a rat model of STC with Qi Stagnation Pattern, established using the “loperamide + tail-clamping provocation method,” to explore the effects of LTD on fecal characteristics, intestinal motility, and colonic pathology. Importantly, LTD exhibited the ability to increase the richness, diversity, and homogeneity of intestinal flora while also modulating the composition of microorganisms. It significantly increased the production of SCFAs, especially butyric acid. Moreover, LTD exerted a substantial influence on the synthesis of serotonin (5-HT) by modulating the expression of tryptophan hydroxylase (TPH) and interacting with the 5-HT4 receptor (5-HT4R), resulting in enhanced colonic motility. Correlation analyses revealed a positive correlation between certain bacterial genera, such as Lachnospiraceae_NK4A136 spp. and Clostridiales spp. and the concentrations of butyric acid and 5-HT. These results suggest a mechanistic link between microbiome composition, SCFAs production, and 5-HT synthesis. These findings highlight the potential of LTD to alleviate STC by facilitating a beneficial interplay among intestinal flora, SCFAs production, and 5-HT-mediated colonic motility, providing novel insights into the management of STC with Qi Stagnation Pattern.